Using Simulation for Anesthesia Crisis Management in The Undergraduate Curriculum: Systematic Literature Review - Abaalkhayl, Mohammed (International Journal of Membrane Science and Technology, 2023)
This literature review aims to shed light on the present status of simulation-based training for anesthesia crisis management in undergraduate medical education and suggest prospective areas for further study and improvement. This research study will implement a PICO formula to facilitate the search strategy’s organized documentation. The study selection was performed using the EBSCOhost, and ScienceDirect to find studies that investigated the use of simulation in anesthesiology. The search strategy involved combining the keywords using the Boolean operator "AND" to refine the search and ensure the retrieval of relevant articles. After the inclusion and exclusion criteria, 15 studies were included. In this systematic review. The search was limited from 2018 to 2023 in both databases. Finally, Using simulation for anesthesia crisis management in undergraduate curricula effectively improves the performance of non-technical skills, such as situational awareness, decision-making, communication, and teamwork. The long-term effects of simulation-based training on clinical results and patient safety also need further investigation.